PERAN SEGMENTASI BAGI BUSINESS TO BUSINESS UNTUK MENCAPAI KEUNGGULAN BERSAING - VALENTINA S, LANI (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This paper aims to discuss the role of segmentation for business to business to achieve competitive advantage. Segmentation has a role to determine the business to business strategy in order to achieve a competitive advantage with the ability to determine the appropriate target market with the resources the business to business. Segmentation makes business to business can focus on a particular consumer group that brings the ability to create effectiveness in order to achieve cost leadership. Business to business is also able to create a better differentiation because it is more focused on particular groups. Changes in the environment, create business to business should be an evaluation of the segmentation is performed. This is due to changes in the environment allows a shift in the characteristics that ultimately led to a shift in the segment grouping.